Faktor-Faktor Penentu Adopsi Teknologi Pemanfaatan Limbah Ternak Sapi Menjadi Pupuk Kandang di Kalurahan Sidorejo, Kapanewon Lendah - Devita, Devita Putri Kunanti; Hermawan, Hermawan; Fauziah, Nicky Oktav (Journal of Agribusiness Science and Rural Development, 2025)
Cow manure in Sidorejo Village, Lendah District, has yet to be effectively utilized for the production of organic fertilizer. This study aims to understand the contribution of internal factors, external factors, and innovation characteristics to the adoption level among farmers in utilizing cow manure for organic fertilizer production in Sidorejo Village, Lendah District. This study involved 64 farmers as respondents, selected using proportional random sampling technique. The study employed a quantitative approach using inferential statistics through multiple linear regression analysis. The study found that variables significantly influencing the adoption level of cow manure utilization for organic fertilizer include the role of farmer group leaders, the role of extension agents, perceived relative advantage, compatibility, trialability, and observability. Meanwhile, the study shows that age, education, farming experience, and compatibility do not have a significant influence on the adoption level of cow manure utilization for organic fertilizer. These findings highlight the importance of utilizing cow manure as organic fertilizer to benefit the soil and crops, while reducing excessive use of chemical fertilizers. Therefore, it is recommended that farmers be willing to embrace new knowledge and gradually move away from the old habit of leaving livestock waste untreated. Additionally, support from local extension agents is needed to disseminate knowledge about utilizing cow manure as organic fertilizer, ensuring that farmers receive this information evenly.